Effect of slope on the forest structure of the Atlantic Forest domain in southern Brazil - Souza,D. C. (2024)
Abstract The mosaic landscape composition of forest fragments located on high slopes, shallow soils hinder ecological interactions and the survival of plant species. This study aimed to show, in an environment with these characteristics, the effect of the environmental gradient relating the soil, slope, and vegetation of a fragment of the Montane Seasonal Semideciduous Forest. The forest structure was sampled in 12 continuous rectangular plots, with 30 X 20m, totaling 0.72ha. Soil samples were taken by drilling every 20m along the hydrographic divisor and opening of three trenches used as soil sampling sites for in situ determination of soil color, horizon, and nutrients. Horizons were classified as O/A/Cr in the altered rock with a marked presence of gravels, and the soil was classified as Litholic Neosol. The area has a steep slope, from 18.05% to 36.99%. Linear regression analysis indicated an opposite pattern for species richness in relation to slope and a positive relationship between slope and the number of standing dead individuals. Species richness was also positively related to the distance from forest edges. The evaluation evidenced the strong influence of slope and human activities in forest remnant as common to several high-altitude remnants, and small conservation actions can guarantee their maintenance.